Small-town Russia : postcommunist livelihoods and identities : a portrait of the intelligentsia in Achit, Bednodemyanovsk and Zubtsov, 1999-2000 - White, Anne, 1959- (BASEES/RoutledgeCurzon series on Russian and East European studies, 2004)
This book examines a number of key questions about social change in contemporary Russia - issues such as how people survive when they are not paid for months on end, 'the New Poor', the falling birth rate, why so many Russian men die in middle age, whether regional identities are becoming stronger, and how people's sense of 'Russianness' has developed since the creation of the Russian Federation in 1992.